Connecting RDM Services: Interoperability and Interfaces for RDMO - Windeck, Jürgen; Schröder, Max; Frenzel, Johannes; Kusmierz, Stefan; Fuchs, Hannes; Klar, Jochen (Bausteine Forschungsdatenmanagement, 2024)
The Research Data Management Organiser (RDMO) supports researchers in the creation of data management plans (DMPs). The open source software has established itself widely across Germany as the standard DMP tool. For its broader adoption, integration with other services for research data management is key. In this paper we reflect on the potential of RDMO on this issue, we explain its adaptiveness by design, its plugin architecture, and report on the first RDMO Hackathon organized in Darmstadt in Aug 2023 which focussed on the integration of RDMO via plugins. We present three extensions and plugins developed during the hackathon: 1.) a JSON-editor for RDMO data transfer and mapping, 2.) an RO-crate export plugin, 3.) a sensor database option set plugin.